A new genus of Paguridae (Crustacea: Decapoda: Anomura) for a new species from the tropical eastern Pacific and Pagurus longimanus Wass, 1963 from the tropical western Atlantic - Lemaitre, Rafael; Felder, Darryl L. (Zootaxa, 2011)
A new genus, Spathapagurus, is described for S. collinae n. sp. from the tropical eastern Pacific and its geminate species Pagurus longimanus Wass, 1963 from the tropical western Atlantic. These congeners share grossly unequal chelipeds, the right being narrowly spatulate and up to four times longer than the left. The males have short sexual tubes consisting of slight extrusions of the vas deferens from the gonopores, though these short tubes are masked by long, forwardly directed setae. The females lack first pleopods and have unpaired left second to fifth pleopods. The new species is fully described, illustrated, and compared to P. longimanus, herein placed in the new genus. The diagnosis of the latter species is emended and its distribution expanded to include the Caribbean coast of Panama in Central America.